Kepuasan Konsumen Terhadap Kualitas Pelayanan Di Apotek Karunia Sehat Baru Berdasarkan Nilai-Nilai Syariah - Fathnin, Fildza Huwaina; Sunandari, Agustina; Mumpuni, Wanda (Sultan Agung Islamic University of Semarang, 2023)
Background: Public health can be maintained and improved by providing good pharmaceutical services. Pharmaceutical services are currently required to change from focusing on products to focusing on patients. Islam emphasizes a quality service, namely the existence of a sense of satisfaction received by others because of the services provided. Based on this background, this study aim to conduct research on consumer satisfaction with the quality of service at the Karunia Sehat Baru Pharmacy based on sharia values. Methods: This type of research is descriptive observational with prospective data collection. The research was conducted at Karunia Sehat Baru Pharmacy. The subjects of this research were 30 consumers of Karunia Sehat Baru Pharmacy using purposive sampling technique. Data collection uses a questionnaire which is composed of 5 aspects, reliability, responsiveness, assurance, empathy, and tangible, on the basis of shidiq, amanah, tabligh, fatonah, which are tested for validity and reliability. Results: Consumer satisfaction with services at the Karunia Sehat Baru Pharmacy based on sharia values obtained an average index value of 97.98%, on the assurance dimension of 97.32%, the responsiveness dimension is 97.3%, the empathy dimension is 94.66%, and the tangibles dimension is 96.66%. Conclusion: The average level of satisfaction of respondents is included in the high category. These results provide input to the Karunia Sehat Baru Pharmacy to continue to maintain services so that consumers continue to get satisfaction, which can be in the form of making standards related to sharia values.